2005
DOI: 10.1063/1.1863446
|View full text |Cite
|
Sign up to set email alerts
|

Negative differential resistance and electroluminescence from InAs light-emitting diodes grown by liquid-phase epitaxy

Abstract: Negative differential resistance has been observed from InAs homojunction light-emitting diodes grown using liquid-phase epitaxy at 455°C. The devices were characterized using current–voltage (I–V) and electroluminescence spectroscopy measurements to obtain information about structure defects in InAs. Two distinct negative differential resistance regions were observed in the forward bias I–V characteristic, consistent with carriers tunnelling into defect levels within the InAs band gap. At large forward bias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…12 Relatively few experimental studies on electrical conduction through defects have been reported. 13 Research on defects has focused on the optical properties and microstructures. 14,15 In this study, negative differential resistance ͑NDR͒ behavior was observed when measuring the electrical properties of defective single crystalline GaN nanowires.…”
mentioning
confidence: 99%
“…12 Relatively few experimental studies on electrical conduction through defects have been reported. 13 Research on defects has focused on the optical properties and microstructures. 14,15 In this study, negative differential resistance ͑NDR͒ behavior was observed when measuring the electrical properties of defective single crystalline GaN nanowires.…”
mentioning
confidence: 99%
“…As an important infrared material, InAs (band gap 0.36 eV at room temperature) has been used to fabricate various infrared optoelectronic devices such as detectors and light emitting diodes. [10,11] In this study, an infrared-sensitive InAs solar cell is fabricated and its current-voltage characteristics in the dark and under AM1.5 illumination at 300 K and 77 K are investigated.…”
mentioning
confidence: 99%